Influence of Joint Impairments on Walking in Children with Cerebral Palsy - Atsuta, Yuji; Mita, Katsumi; Watanabe, Makoto; Takemitsu, Yoshiharu; Suzuki, Nobuharu; Asakura, Toshimitsu (Nihon Kikai Gakkai ronbunshū. C, 1995)
The restriction of the range of motion (ROM) of joints in patients with cerebral palsy (CP) is caused by joint contracture and muscle shortening due to the effects of their disease on the brain. The aim of this study is as to identify the influence of the restricted ROM of joints on walking ability in CP children by means of simultaneous measurements of oxygen consumption, acceleration of body in the vertical direction, stride and cadence during walking on a treadmill. The stride and cadence in CP children were similar to those in normal children. The CP children demonstrated greater oxygen consumption and acceleration compared with normal subjects ; in particular, this trend was more marked in CP group members with restriction of joint movement. These findings suggest the joint impairment contributes to walking disability as well as dysfunction in the neuromuscular system. When the motion of the ankle joints in normal children was restricted with a pair of special short braces, the children exhibited the kind of impaired walking seen in CP children, although the degree of the disability was not as great as that in CP patients. These results also seem to support the close relationship between the joint impairment and walking disability.